The code [videorecording (DVD)] - Cooter, Stephen; Lachmann, Michael, 1946-; Child, Dan; Du Sautoy, Marcus (Athena ; Distributed by Acorn Media, 2012)
Author and Oxford University professor Marcus du Sautoy sets out to solve mathematical mysteries in an engaging and accessible BBC documentary. Du Sautoy travels from Chartres Cathedral to Grand Central Station in search of the mysterious hidden code that can unlock the very laws of the universe.